Unrecognized neuromyelitis optica spectrum disorder with pontine and corpus callosum microhemorrhage: English - Nosek, Igor; Boban, Jasmina; Vlahović, Dmitar; Radovanović, Biljana; Kostić, Dejan; Kozić, Duško (Vojnosanitetski pregled, 2023)
Introduction. Neuromyelitis optica spectrum disorder (NMOSD) represents an immune-mediated neuroinflammatory syndrome, classified as a separate entity after the discovery of aquaporin-4 immunoglobulin G (anti-AQP4-IgG). The magnetic resonance neuroimaging spectrum of NMOSD classically consists of bilateral optic neuritis and longitudinally extensive transverse myelitis (LETM), recently broadened with lesions in area postrema, diencephalon, brainstem and cerebellum, and extensive cord atrophy. Case report. The case presents an anti-AQP4 autoantibody-positive 65-year-old female patient who initially presented with underestimated LETM and developed multiple cerebral and cerebellar lytic demyelinating lesions associated with acute long segment optic nerve involvement two years later. Two new imaging findings were described in this case: the involvement of a complete cross-sectional area of pons and microhemorrhage in the pons and corpus callosum. Conclusion. Raising suspicion of NMOSD is of crucial importance in cases with isolated LETM in order to prevent relapses in anti-AQP4-IgG positive cases and improve patient outcomes and recovery.
Keywords: anti-aquaporin 4 autoantibody; magnetic resonance imaging; neuroinflammatory diseases; neuromyelitis optica; treatment outcome